2022
DOI: 10.21037/qims-21-1174
|View full text |Cite
|
Sign up to set email alerts
|

Application of 18F-NaF-PET/CT in assessing age-related changes in the cervical spine

Abstract: Background: Cervical spondylosis is the degeneration of cervical spine often associated with aging and neck pain. As the degenerative changes are coupled with altered osteoblastic activity, imaging modalities sensitive to such molecular changes could be valuable for clinical assessment, disease prophylaxis, and monitoring early therapy response. In this study, we examined the role of 18 F-sodium fluoride-positron emission tomography/computed tomography ( 18 F-NaF-PET/CT) in detecting age-associated changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…NaF uptake has been shown to increase with age in the cervical spine, which may reflect NaF uptake from osteoarthritic structures that are primarily osteoblastic. 21 In contrast, Win and Aparici 22 found no correlation between NaF uptake in the L2 spine and age whereas Kurata et al 23 found a significant negative correlation between NaF uptake in the L3 vertebral body and age in pre/postmenopausal women. Such apparent inconsistency within the literature may reflect that NaF uptake is influenced by both the region of the bone analyzed and the method of analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…NaF uptake has been shown to increase with age in the cervical spine, which may reflect NaF uptake from osteoarthritic structures that are primarily osteoblastic. 21 In contrast, Win and Aparici 22 found no correlation between NaF uptake in the L2 spine and age whereas Kurata et al 23 found a significant negative correlation between NaF uptake in the L3 vertebral body and age in pre/postmenopausal women. Such apparent inconsistency within the literature may reflect that NaF uptake is influenced by both the region of the bone analyzed and the method of analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown mixed results regarding the association between age that NaF uptake with various regions of the body being analyzed. NaF uptake has been shown to increase with age in the cervical spine, which may reflect NaF uptake from osteoarthritic structures that are primarily osteoblastic 21 . In contrast, Win and Aparici 22 found no correlation between NaF uptake in the L2 spine and age whereas Kurata et al 23 found a significant negative correlation between NaF uptake in the L3 vertebral body and age in pre/postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quercetin and kaempferol were found to significantly increase COX-2 gene expression, while the former also showed significant upregulation of IL-1β gene expression in osteoblasts. 39,40 In addition, luteolin and quercetin can restrict the messenger RNA (mRNA) expression of MMP-9 and MMP-13 in osteoblasts, safeguarding their inhibitory effects. 41 Mechanistically, tanshinone IIA, the key active ingredient in SYMGD, inhibited the RANKL-mediated activation of NF-κB, MAPK, and Akt signaling pathways during osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, [ 18 F]NaF was initially used solely for detecting bone metastases. However, with advancements in technology and widespread clinical adoption, [ 18 F]NaF has also demonstrated notable accomplishments in the diagnosis and monitoring therapy of bone diseases, cardiovascular conditions, and other fields ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%